2003
DOI: 10.1890/0012-9658(2003)084[1101:ctaeso]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Theoretical and Empirical Studies of Trait-Mediated Interactions

Abstract: Trait-mediated interactions (TMIs), in which trophic and competitive interactions depend on individual traits as well as on overall population densities, have inspired large amounts of research, but theoretical and empirical studies have not been well connected. To help mitigate this problem, we review and synthesize the theoretical literature on TMIs and, in particular, on trait-mediated indirect interactions, TMIIs, in which the presence of one species mediates the interaction between a second and third spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
343
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(355 citation statements)
references
References 153 publications
(294 reference statements)
7
343
1
4
Order By: Relevance
“…However, there is an increasing interest in the effects of plasticity on population dynamics, and early ideas are being re-discovered or investigated for different types of plasticity. For example, a variety of inducible defenses and offenses can affect the amplitude of population fluctuations, and increase the stability of a population within a community with two or three trophic levels [31][32][33][34][35][36][37][38]. Plasticity can stabilize a population because plastic responses are often density dependent.…”
Section: Altered Interactions Have Consequences For Populations and Cmentioning
confidence: 99%
“…However, there is an increasing interest in the effects of plasticity on population dynamics, and early ideas are being re-discovered or investigated for different types of plasticity. For example, a variety of inducible defenses and offenses can affect the amplitude of population fluctuations, and increase the stability of a population within a community with two or three trophic levels [31][32][33][34][35][36][37][38]. Plasticity can stabilize a population because plastic responses are often density dependent.…”
Section: Altered Interactions Have Consequences For Populations and Cmentioning
confidence: 99%
“…To address this issue, one must examine how antagonistic phenotypic plasticity has coevolved and is maintained in a focal predator-prey interaction. Previous theoretical models have focused on either the inducible defense or offense and have concluded that both types of plasticity can stabilize predator-prey population dynamics (Abrams 1984(Abrams , 1992(Abrams , 1995Matsuda et al 1993Matsuda et al , 1994Matsuda et al , 1996Abrams and Matsuda 1997;Bolker et al 2003;Kondoh 2003Kondoh , 2007Ramos-Jiliberto 2003;Vos et al 2004a,b;Kopp and Gabriel 2006;DeAngelis et al 2007;Mougi and 18 Nishimura 2007, 2008a, 2009. However, few studies have specifically focused on reciprocity in plasticity for both the predator and its prey and behavioral reciprocity has received more attention than morphological reciprocity (Abrams 1992;van Baalen and Sabelis 1993;Adler and Grünbaum 1999;Kokko and Ruxton 2000;Abrams 2007;Krivan 2007;Krivan et al 2008;Mougi and Nishimura 2008b; but see Mougi and Kishida 2009).…”
Section: Reciprocity Of Antagonistic Inducible Phenotypesmentioning
confidence: 99%
“…Theory suggests that such plasticity can promote species coexistence and stabilize population dynamics (Matsuda et al 1993;Bolker et al 2003) as well as provide insight into the paradox of enrichment (Vos et al 2004a,b;Mougi and Nishimura 2007, 2008a, b, 2009) and the complexity-stability debate (Kondoh 2003(Kondoh , 2007. Many empirical studies have documented the importance of trait-mediated indirect effects in three species food chains (see Werner and Peacor 2003;Schmitz et al 2004) via their influence on trophic cascades (Trussell et al , 2006aSchmitz et al 2004) and ecosystem function (Trussell et al 2006bSchmitz et al 2008).…”
mentioning
confidence: 99%
“…There may then be only a weak relationship between numbers of predators and prey population, or with the number of prey directly killed by predators (Abrams 1993). The relative strength of non-lethal effects, their predominance in determining population and community effects, and the decoupling of number of prey killed and predator abundance from the strength of these effects is very well established in the ecological literature (Lima 1998;Agrawal 2001;Bolker et al 2003;Krivan and Schmitz 2004;Schmitz et al 2004;Preisser et al 2005). …”
Section: Introductionmentioning
confidence: 99%